Both youth and long-term vitamin D status is associated with risk of type 2 diabetes mellitus in adulthood: a cohort study - Feitong Wu; Markus Juonala; Niina Pitkänen; Antti Jula; Terho Lehtimäki; Matthew A. Sabin; Katja Pahkala; Nina Hutri-Kähönen; Mika Kähönen; Tomi Laitinen; Jorma S. A. Viikari; Costan G. Magnussen; et al. (Taylor and Francis Ltd, 2025)
Objectives: To determine whether vitamin D status in childhood and adolescence (herein collectively
referred to as youth) and the long-term status from youth to adulthood is associated
with risk of developing type 2 diabetes mellitus (T2DM) and impaired fasting glucose (IFG) in
adulthood.
Materials and methods: This was a 31-year follow-up study of 2300 participants aged 3–18
years. Multinomial logistic regression was used to assess the association of both (a) baseline 25-
hydroxyvitamin D (25OHD) levels and (b) the mean of baseline and the latest follow-up 25OHD
levels (continuous variable and quartiles) with incident T2DM and IFG (cut-off¼5.6mmol/L) in
adult life.
Results: High serum 25OHD levels in youth and also mean values from youth to adulthood
were associated with reduced risk of developing T2DM in adulthood (odds ratio, 95% confidence
interval¼0.73, 0.57–0.95 and 0.65, 0.51–0.84, respectively, for each SD increment in 25OHD).
Compared to Q1, a dose-dependent negative association was observed across other quartiles of
youth 25OHD, while the strongest association was found in the Q3 for the mean 25OHD levels.
Neither youth nor the mean 25OHD was associated with IFG.
Conclusions: High serum 25OHD levels in youth, and from child to adult life, were associated
with a reduced risk of developing T2DM in adulthood.
KEY MESSAGES
High serum 25OHD levels in youth, and between youth and adulthood, were associated with
a lower risk of T2DM in adulthood.
Each SD (15.2 nmol/L) increment in youth serum 25OHD levels was associated with a 26%
reduction in odds for T2DM, which was independent of a number of confounding variables
and other risk factors for T2DM. A similar magnitude of association was observed for the
long-term 25OHD levels between youth and adulthood.
These findings suggest a potentially simple and cost-effective strategy for reducing adulthood
risk of T2DM starting in an earlier stage of life – improving and maintaining vitamin D status
throughout youth and early adulthood.